Finitary groups and Krull dimension over the integers - Wehrfritz, B. A. F. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
Let $M$ be any Abelian group. We make a detailed study for reasons explained in the Introduction of the normal subgroup$$F_∞ Aut M = \{ g \in Aut M: M(g - 1) is\;a \;minimax\; group\}$$of the automorphism group $Aut M$ of $M$. The conclusions, although slightly weaker than one would hope, in that they do not fully explain the common behavior of the finitary and the Artinian-finitary subgroups of $Aut M$, are certainly stronger than one might reasonably expect. Our main focus is on residual properties and unipotence.